A New Clinically Driven Classification for Acute Aortic Dissection - Qanadli, Salah D.; Malekzadeh, Sonaz; Villard, Nicolas; Jouannic, Anne-Marie; Bodenmann, Daniel; Tozzi, Piergiorgio; Rotzinger, David C. (Frontiers in Surgery, 2020)
Objectives To report a new classification scheme for acute aortic dissection (AAD) that considers the aortic arch as a separate entity and integrates patterns of malperfusion syndrome (MPS). The proposed classification was evaluated retrospectively in a large population. Materials and Methods We retrospectively reviewed pre-therapy CT angiograms of 226 consecutive patients (mean±SD age: 64±12 years) with AAD. AADs were reclassified with a new classification scheme that included three aortic dissection types (A, involving at least the ascending aorta; B, involving exclusively the descending aorta; and C, involving the aortic arch with/without the descending aorta) and four malperfusion grades (0: no MPS; 1: dynamic MPS; 2: static MPS; 3: static and dynamic MPS). AAD features were assessed and correlated to patient outcomes. Results According to the new classification, we identified 152 type A dissections (92 A0, 11 A1, 38 A2, 11 A3); 50 type B (38 B0, 5 B1, 6 B2, 1 B3); and 24 type C (17 C0, 6 C2, 1 C3). Type C represented 11% of all AADs. MPS occurred in 34%, 24% and 29% in type A, B and C, respectively. Type C was treated with significantly more endovascular or hybrid interventions (37%) than in types A (7%) and B (10%) (p<0.001). Conclusion The new AAD classification was feasible, and type C was easily identified (“non-A, non-B”). Preliminary findings supported the usefulness of this classification for the decision-making process and subsequent treatments.